Estimation of phosphorus isotherm parameters: a simple and cost-effective procedure - Dari, Biswanath; Nair, Vimala D.; Colee, James; Harris, Willie G.; Mylavarapu, Rao (Frontiers in Environmental Science, 2015)
Equilibrium models used for predicting phosphorus (P) loss from a site often use the Langmuir strength of P bonding, KL and the P sorption maximum, Smax, or the Freundlich adsorption coefficient, KF, obtained from traditional isotherms, as model input parameters. The overall objective of the study was to develop a protocol to allow estimation of isotherm parameters for soils using simple extraction techniques without generating time-consuming isotherms. A threshold P saturation ratio (PSR; molar ratio of P to [Fe+Al] in an oxalate- or soil test extracting solution) is the PSR value at which P release from a soil increases abruptly. The soil P storage capacity (SPSC) indicates the amount of P a soil can hold before becoming an environmental risk: SPSC = (Threshold PSR-Soil PSR)*(Fe+Al)*31 mg kg-1. Soil samples with varying P-impact levels from four manure-impacted sites were collected by horizon (Ap, E and Bt). The PSR, SPSC and isotherm parameters (KL, KF, Smax) were determined for all soils and regression equations among various parameters evaluated. Equations were validated with soils data from three other sites. Relationship between predicted and determined parameters were significant (R2 = 0.98 for both KL and KF; 0.95 for Smax) suggesting that isotherm parameters can be obtained from P, Fe and Al in an oxalate or soil test solution without generating time- and resource-consuming isotherms.